2016
DOI: 10.1080/19336934.2016.1225634
|View full text |Cite
|
Sign up to set email alerts
|

Trans-inactivation: Repression in a wrong place

Abstract: Trans-inactivation is the repression of genes on a normal chromosome under the influence of a rearranged homologous chromosome demonstrating the position effect variegation (PEV). This phenomenon was studied in detail on the example of brown Dominant allele causing the repression of wild-type brown gene on the opposite chromosome. We have investigated another trans-inactivationinducing chromosome rearrangement, In(2)A4 inversion. In both cases, brown Dominant and In(2)A4, the repression seems to be the result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The performed analysis indicated that Myb is located at the base of chromosome X near the chromocenter in D. virilis, which is apparently a part of the pericentric heterochromatin ( Figure 1 B). A distinctive well-known feature of heterochromatin is the ability to silence euchromatic genes placed within the heterochromatic environment, a phenomenon called position effect variegation (PEV) [ 2 , 44 ]. In spite of the silencing effect of PEV, these protein-coding genes are actively transcribed, according to the RNA-seq mapping profile which shows expression predominantly of the exonic regions of the genes ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
“…The performed analysis indicated that Myb is located at the base of chromosome X near the chromocenter in D. virilis, which is apparently a part of the pericentric heterochromatin ( Figure 1 B). A distinctive well-known feature of heterochromatin is the ability to silence euchromatic genes placed within the heterochromatic environment, a phenomenon called position effect variegation (PEV) [ 2 , 44 ]. In spite of the silencing effect of PEV, these protein-coding genes are actively transcribed, according to the RNA-seq mapping profile which shows expression predominantly of the exonic regions of the genes ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
“…A distinctive feature of heterochromatin is the ability to silence euchromatic genes placed within heterochromatic environment due to chromosomal inversions or transposition events, a phenomenon called position effect variegation (PEV) 7 12 . It is generally believed that transcriptional silencing of euchromatic genes in PEV is mediated by spreading of heterochromatin-associated marks HP1a and H3K9me3 across the gene loci transferred to heterochromatin 8 , 10 .…”
Section: Introductionmentioning
confidence: 99%
“…A distinctive feature of heterochromatin is the ability to silence euchromatic genes placed within heterochromatic environment due to chromosomal inversions or transposition events, a phenomenon called position effect variegation (PEV) (7-12). Transcriptional silencing of euchromatic genes in PEV is mediated by spreading of heterochromatin-associated marks HP1a and H3K9me3 across the gene loci transferred to heterochromatin (8,10).…”
Section: Introductionmentioning
confidence: 99%